Pengaruh Pendapatan Desa Dan Alokasi Dana Desa Terhadap Kesejahteraan Masyarakat Desa : Studi Kasus Desa Pulau Kecil - Rosmiati Rosmiati; Titin Agustin Nengsih; Muhammad Subhan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The purpose of this study was to determine the effect of village income and village fund allocation partially and simultaneously on the welfare of rural communities in Pulau Kecil Village. The type of research used in this research is descriptive quantitative research. The sampling method in this research is using purposive sampling. Methods of data collection using observation, questionnaires, and documents. Methods of data analysis using Descriptive Analysis and Multiple Regression Analysis. The results show that: (1) The village income variable has a significant effect on the welfare of the Small Island Village community. If village income increases, the welfare of the Small Island Village community, (2) The village fund allocation variable has a significant effect on the welfare of the Small Island Village community. If the allocation of village funds is properly allocated, the welfare of the Small Island Village community will also increase, (3) The village income variable and the allocation of village funds have a significant effect on the welfare of the Small Island Village community.